1986
DOI: 10.1093/nar/14.21.8595
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing and identification of a cDNA done for tomato polygalacturonase

Abstract: The 2a isoenzyme of tomato polygalacturonase was purified from ripe fruit and characterised. The N-terminal amino acid sequence of the protein was determined in order to identify polygalacturonase cDNA clones. The nucleotide sequence of a ripening-related cDNA (pTOM 6) was determined and found to encode the N-terminal sequence of mature polygalacturonase 2a. The complete open reading frame encodes a polypeptide of molecular weight 50,051, including a putative pre-sequence of 71 amino acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
87
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(90 citation statements)
references
References 13 publications
3
87
0
Order By: Relevance
“…The calculated molecular mass of the deduced mature PGII is 35 kDa, which agrees well with experimental data [3]. An alignment of the sequences of the mature PGII and the mature tomato PG [15,16] indicates a low (27010) but significant homology and also confirms the presence and location of the intron in the pgaI1 gene (not shown). GAAGCTCGAGACAGCTGCACGTTCACCACCGCTGCCGCTGCTAAAGCGGGCAAGGCGAAATGCTCTACTATC 144 **********************R*****C*******t* Fig.…”
Section: Manipulation Of Dnasupporting
confidence: 85%
“…The calculated molecular mass of the deduced mature PGII is 35 kDa, which agrees well with experimental data [3]. An alignment of the sequences of the mature PGII and the mature tomato PG [15,16] indicates a low (27010) but significant homology and also confirms the presence and location of the intron in the pgaI1 gene (not shown). GAAGCTCGAGACAGCTGCACGTTCACCACCGCTGCCGCTGCTAAAGCGGGCAAGGCGAAATGCTCTACTATC 144 **********************R*****C*******t* Fig.…”
Section: Manipulation Of Dnasupporting
confidence: 85%
“…Subsequently, Pogson and Brady (1993a) prepared antibodies to the ft subunit and to PG1 but found these antibodies to have extensive cross-reaction with PG2, which necessitated preadsorption to PG2 before their use. We prepared antibodies to the ft subunit, but our antiserum did not appear to cross-react with PG2, which is consistent with the lack of homology between the ft subunit gene (Zheng et al, 1992) and PG2 (Grierson et al, 1986;Bennett and DellaPenna, 1987). Anti-0 subunit antibodies detected a protein in green fruit, consistent with the presence of a converter activity in this tissue (Tucker et al, 1981) and consistent with the presence of the mRNA for this protein at this stage in fruit development (Zheng et al, 1992).…”
Section: Tomato Fruit Converter Activity and Characterization Of The supporting
confidence: 71%
“…However, searching the SWISS-PROT database revealed that the Cryj II amino acid sequence shares a significant homology with polygalacturonases (PGs), especially that derived from tomato, Lycopersicon esculentum (40% identity, Fig. 2) [14,15], from Zea mays (34% identity) [16,17], and that from Oenothera organensis (34% identity) [18].…”
Section: Resultsmentioning
confidence: 99%